2021
DOI: 10.3389/fneur.2021.650532
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Tolerability, and Effect of Nusinersen in Non-ambulatory Adults With Spinal Muscular Atrophy

Abstract: Objective: Investigation of the safety, tolerability, and treatment effect of nusinersen treatment in non-ambulatory adults with spinal muscular atrophy (SMA).Methods: Non-ambulatory individuals, aged 18 years or older with genetically confirmed 5q SMA were enrolled. In participants with spinal fusion, fluoroscopy guided cervical C1–C2 lateral approach was used. Outcomes at 2, 6, 10, and 14 months post-treatment were compared with baseline assessment. Forced vital capacity (FVC) was the primary outcome, and RU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 28 publications
3
17
0
Order By: Relevance
“…Therefore, in our study nusinersen increased motor unit function but not number in adults with SMA. In a parallel study in non-ambulatory adults with SMA, we found a similar pattern of increases in CMAP and SMUP and stable MUNE (31). Interestingly, in a recent study that used MscanFit MUNE to estimate motor unit number in children with SMA treated with nusinersen, it was shown that nusinersen induced recovery of smaller motor units (32).…”
Section: Physiological Impact Of Nusinersen On Motor Unit Functionsupporting
confidence: 69%
“…Therefore, in our study nusinersen increased motor unit function but not number in adults with SMA. In a parallel study in non-ambulatory adults with SMA, we found a similar pattern of increases in CMAP and SMUP and stable MUNE (31). Interestingly, in a recent study that used MscanFit MUNE to estimate motor unit number in children with SMA treated with nusinersen, it was shown that nusinersen induced recovery of smaller motor units (32).…”
Section: Physiological Impact Of Nusinersen On Motor Unit Functionsupporting
confidence: 69%
“…This substudy was performed as part of two prospective, open-label studies (clinicaltrials.gov: NCT04139343 and NCT04591678) that were conducted at the Ohio State University Wexner Medical Centre between June 2017 and January 2020. 19 20 Data collection for this substudy was conducted between May 2019 and October 2020. All procedures were approved by the institutional review board, and before enrolment, written informed consent was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Several other motor scales have been used for nonambulatory SMA patients (eg, Hammersmith Functional Rating Scale‐Expanded, Revised Upper Limb Module, Motor Function Measure, etc). These tests can be difficult to perform in debilitated individuals, and all have limitations for detecting subtle but potentially meaningful changes in SMA patients with advanced disease 8,15,40 . This underscores the need for more refined outcome measures in the era of multiple disease‐modifying therapies for SMA 41 …”
Section: Discussionmentioning
confidence: 99%
“…These tests can be difficult to perform in debilitated individuals, and all have limitations for detecting subtle but potentially meaningful changes in SMA patients with advanced disease. 8,15,40 This underscores the need for more refined outcome measures in the era of multiple disease-modifying therapies for SMA. 41 Plasma pNF-H concentrations and CMAPs, biomarkers used to track SMA disease severity in infants, 26,42,43 were already very low in patients from the older SIC cohort.…”
Section: Pulmonary Infection 4mentioning
confidence: 99%
See 1 more Smart Citation